Growth response of Catlacatla (Hamilton,1822) raised in manured tanks on low fishmeal diets,with a note on carcass composition and digestive enzyme activity - Manjappa, K.; Keshavanath, P.; Gangadhar, B. (Indian Journal of Fisheries, 2016)
Low fishmeal diets (10%) with varied levels of maize (40-31%) and sardine oil (0-9%) were fed for 120 days to triplicate groups of catla (Catla catla Hamilton,1822) fingerlings (average weight 1.84-1.90 g) stocked @ 1 fish per m2 in cement tanks with soil base fertilised with poultry manure. Fish fed on diet containing 6% oil and 34% maize (T2) showed the highest (p<0.05) growth, followed by those received 9/31 (T3), 3/37 (T1) and 0/40% (T0) oil/maize supplemented diets. Food conversion ratio improved due to oil supplementation, while protein efficiency ratio was not affected significantly. Dietary lipid had a positive impact on carcass protein and lipid levels (p<0.05). Fish survival ranged from 90.73% in all the treatment groups to 92.58% in the control, without any significant (p>0.05) difference among them. Net fish production on termination of the experiment was lowest (820 g) in the control and the highest (1017.85 g) inT2 treatment. Viscerosomatic index (VSI) varied from 3.59 (T2) to 4.65% (T0) and hepatosomatic index (HSI) from 1.13 (T0) to 1.91% (T3). RNA/DNA ratio was highest (3.05) in T2 and lowest (1.84) in T0. An increase in intestinal amylase activity was observed in the treated fish, while intestinal protease and lipase activity showed increase only with higher levels of oil supplementation (6 and 9%). No difference (p>0.05) in enzyme activity was observed in the hepatopancreas of the control and treated fish. The results indicated beneficial effects of incorporating maize and fish oil in low fishmeal diet for catla.